Changing Research Behaviours of University Students with Progression throughout a Course. Issue 3 (3rd July 2018) - Qayyum, Dr. M. Asim; Smith, Dr. David
ABSTRACT: The purpose of this study was to learn from a comparison of assessment related research behaviour of novice and experienced university students by investigating their online information searching, reading, and resource use practices. Significance is that changing online learning environments require a rethink of traditional learning and teaching practices, and this study adds practical recommendations to the LIS knowledgebase for designing learning material in virtual environments. For this purpose, published findings from two phases of a study were compiled into comparison tables for this study. Relevant data from original datasets were added to strengthen comparison. Compiled information was assessed by researchers to form three themes; information tools selection, information searching, and information analysis. Results indicate that both groups used a modest suite of information searching tools, and videos and social media were avoided. Experienced students made use of library provided discovery tools, and engaged with and supplemented their searches by using advanced features of the search tool. Both groups engaged in speed reading, but the experienced students were more engaged with online texts, read relatively linearly, and worked with keywords. Recommendations focus on skill development of educators to design online learning materials, and training students to effectively address assessment requirements.